Co-simulation platform for interconnected power systems and communication networks based on PSS/E and OMNeT++. (July 2022) - Ledesma, Pablo; Gotti, Davide; Amaris, Hortensia
Abstract: This paper proposes a co-simulator that combines OMNeT++ for communication systems with PSS/E for the electrical transmission network. The co-simulator applies an event-driven synchronization method that minimizes errors due to delays in the synchronization between both simulators. The synchronization method pauses the simulation of the power system at each communication event, while a supervisory module in PSS/E returns control to the event simulator if any condition from a pre-specified set is met. The proposed co-simulator is demonstrated on a protection system based on peer-to-peer communication and used to evaluate the effect of communication latency times on an online state estimator. Graphical abstract: Highlights: Integration of PSS/E and an event-driven simulator in a single co-simulation platform. Synchronization method that reduces wall-clock simulation time. Simulation of communication systems in large interconnected power systems. Allows the use of dynamic models developed by Transmission System Operators in PSS/E. Assessment of the effect of latency times on a dynamic state estimator based on synchrophasors.